Online learning in schools of business: what influences faculty to teach online?. (3rd April 2022) - Andrade, Maureen Snow; Miller, Ronald Mellado; Kunz, Michelle B.; Ratliff, Janet M.
ABSTRACT: College students today are much more diverse in their needs than in the past (e.g., they may live off campus, work full or part time, and seek ways to lessen college-related debt). Institutions of higher education are seeking ways to more effectively reach this diverse student population, often through online education. Institutions also realise that faculty are a primary contributing factor to whether or not such programs will be successful. This is because faculty selected to develop and teach online are responsible for both content and delivery; thus, they largely control the quality of the courses offered. Since business is one of the most highly sought-after areas of study online, schools of business must find ways to develop and implement online programs, while ensuring quality and meeting accreditation standards. Deans of AACSB-accredited business schools were surveyed in this study to determine their approaches related to faculty participation in online learning initiatives. Specifically, this study examines variables that are associated with faculty participation in online teaching. Through multiple regression analyses, the study examines which elements of practice are significant in this effort.